Enhancing easy-plane anisotropy in bespoke Ni(II) quantum magnets. (1st April 2020) - Manson, Jamie L.; Manson, Zachary E.; Sargent, Ashley; Villa, Danielle Y.; Etten, Nicole L.; Blackmore, William J.A.; Curley, Samuel P.M.; Williams, Robert C.; Brambleby, Jamie; Goddard, Paul A.; Ozarowski, Andrew; Wilson, Murray N.; et al.
Graphical abstract: By design, targeted pseudo-octahedral Ni(II) complexes composed of simple ligands L show easy-plane anisotropy with 8 ≤  D  ≤ 25 K. For small donor-atoms; e.g., N, F, and O, D is the largest for NiN4 F2 and smallest for NiN4 O2 . This correlates with Ni- L ax  ≤ Ni-Neq and the ligand spectro-chemical properties. Abstract: We examine the crystal structures and magnetic properties of several S  = 1 Ni(II) coordination compounds, molecules and polymers, that include the bridging ligands HF2 −, A F6 2− ( A  = Ti, Zr) and pyrazine or non-bridging ligands F −, SiF6 2−, glycine, H2 O, 1-vinylimidazole, 4-methylpyrazole and 3-hydroxypyridine. Pseudo-octahedral NiN4 F2, NiN4 O2 or NiN4 OF cores consist of equatorial Ni-N bonds that are equal to or slightly longer than the axial Ni- L ax bonds. By design, the zero-field splitting ( D ) is large in these systems and, in the presence of substantial exchange interactions ( J ), can be difficult to discriminate from magnetometry measurements on powder samples. Thus, we relied on pulsed-field magnetization in those cases and employed electron-spin resonance (ESR) to confirm D when J  ≪  D . The anisotropy of each compound was found to be easy-plane ( D  > 0) and range from ≈ 8–25 K. This work reveals a linear correlation between the ratio d (Ni- L ax )/ d (Ni-Neq ) and D although the ligand spectrochemical properties may play an important role. We assert that this relationship allows us to predict the type of magnetocrystalline anisotropy in tailored Ni(II) quantum magnets.